Interpersonal Communication Across Disciplines: Mapping DeVito's Model in Virtual Higher Education Through Systematic Literature Review - Aditya Permadi; Ope Destrian; Abdhy Aulia Adnans (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study examines DeVito's Interpersonal Communication Model as an interdisciplinary theoretical framework capable of bridging communication studies, educational science, and digital learning discourse. Grounded in the premise that interpersonal communication is the primary determinant of relational quality in technology-mediated environments, this study conducts a Systematic Literature Review (SLR) of national and international journal articles published between 2013 and 2023, sourced from Google Scholar, Scopus, and ERIC. The review maps how DeVito's five core communication dimensions, openness, empathy, supportiveness, positiveness, and equality, are operationalized across disciplinary boundaries, from educational communication and instructional design to digital sociology and health communication. Findings reveal that while these dimensions consistently appear across the reviewed literature as central factors shaping communicative climate, social presence, and relational engagement in virtual classrooms, they are rarely integrated under a unified communication framework. Scholars from different disciplines address the same relational phenomena through divergent vocabularies, social presence, instructor immediacy, and dialogic feedback, without recognizing their shared theoretical foundation in interpersonal communication theory. This study addresses that fragmentation by proposing a conceptual model that repositions virtual learning as a relational communication process, mediated but not determined by technology. The model demonstrates the interdisciplinary reach of DeVito's framework and contributes to the development of an integrated communication paradigm for digital learning environments.